Achieving social innovation in the digital age: A case study of microbusiness - Wei-Hung Chen; Shi Chen; Yao-Chin Lin; Chun-Liang Chen; Wai-Kit Ng; Yifan Ding; Ying-Shueh Shih; Hsin-Na Chen (International Journal of Innovation Studies)
This study explores the feasibility of micro-enterprise cluster applications in online-to-offline service platforms to better understand the impact of social innovations and information and communications technology (ICT) capabilities in the digital age. We tried to discover the factors that affect micro-enterprises’ social innovations and sustainable development outcomes. The qualitative data analysis method is summarized using exploratory data analysis. This study reveals that the key drivers of social innovation for microbusiness clusters are shared value proposition and actor engagement, as per the multiple cases through interviews and observations. This study emphasizes that online-to-offline (O2O) e-commerce is an important part of service platforms, especially in the application of microbusiness clustering social innovation, because social innovation can impact their sustainable development by enhancing their ICT ability, which can also increase the application level of service platforms. The sustainable development of microbusiness is one type of sustainable transformation. There are four types of social innovations in microbusiness clusters: the Branding model, the customer interaction mode, the collaboration and profit sharing mode, and the sustainable development mode. The driving forces of the social innovations of microbusiness are frugal-driven, socially driven, and sustainability-driven forces.